First Restoration Experiment for Endemic Fucus virsoides on the Western Istrian Coast—Is It Feasible? - Edi Gljušćić; Andrea Bilajac; Shannen Maree Smith; Mirjana Najdek; Ljiljana Iveša (Plants, 2023)
Fucus virsoides is an endemic species of the Mediterranean limited to the Adriatic Sea. In recent decades, it has undergone a severe regression, which is well documented in the northern Adriatic. To develop a tool for mitigating this problem, we tested the feasibility of F. virsoides restoration and designed a very simple yet effective method for ex situ cultivation and planting. We also tested the effect of positioning in the upper vs. lower intertidal on the growth of F. virsoides. After planting, the algae reached fertility in nine months, which was followed by a period of stagnation and reduction in size due to grazing and fouling. There were some differences in growth of the algae according to positioning in the intertidal at different measurement times, but that had little impact on the overall success of the restoration experiment. This represents, to our knowledge, the first successful F. virsoides ex situ cultivation and restoration attempt.